Security a philosophical investigation - Welch, David 1960- (Cambridge University Press, 2022)
How do we know when we are investing wisely in security? Answering this question requires investigating what things are worth securing (and why); what threatens them; how best to protect them; and how to think about it. Is it possible to protect them? How best go about protecting them? What trade-offs are involved in allocating resources to security problems? This book responds to these questions by stripping down our preconceptions and rebuilding an understanding of security from the ground up on the basis of a common-sense ontology and an explicit theory of value. It argues for a clear distinction between objective and subjective security threats, a non-anthropocentric understanding of security, and a particular hierarchy of security referents, looking closely at four in particular-the ecosphere, the state, culture, and individual human beings. The analysis will be of interest not only to students and scholars of International Relations, but also to practitioners